Relationship between maternal perception and full immunization coverage among children aged 1-3 years in Kalibagor Village, Situbondo District - Ifa Nurhasanah; Desak Putu Yuli Kurniati; Dewa Nyoman Wirawan (Universitas Udayana, 2018)
Background and purpose: Full immunization coverage in Indonesia and East Java Province is reported to remain below the target of Universal Child Immunization. The purpose of the study was to determine the association between maternal perception and full immunization coverage among children aged 1-3 years. Methods: A cross-sectional study was conducted with mothers who had children under 3 years in Kalibagor Village, Situbondo District, East Java Province. A total of 116 respondents were selected using systematic random sampling from 133 mothers of children aged 1-3 years. Listing of all mothers was conducted through home visits one month before data collection. Data collection was conducted by interview at respondents' house in October-May 2018. Data collected included sociodemographic characteristics, knowledge on immunization, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, information on immunization, and support from community leader, health provider and peer. Data analysis with logistic regression was conducted to determine the relationship between maternal perception with full immunization coverage. Results: This study showed that 79.3% of respondents reported to have provided full immunization to their children. The results of multivariate analysis showed that full immunization was related to the mother's perception on the benefits of immunization (AOR=59.75; 95%CI: 4.60-775.86), self-efficacy (AOR=6.25; 95%CI: 1.84-21.35) and knowledge on immunization (AOR=7.77; 95%CI: 1.92-31.49). Conclusion: Maternal perceptions on immunization’s benefits, selfefficacy and knowledge are related to the full immunization coverage in children. Education about the benefits of immunization needs to be prioritized in an effort to increase full immunization coverage in children.